THE EFFECTIVENESS OF COGNITIVE STRATEGY INSTRUCTION IN WRITING (CSIW) TO IMPROVE STUDENTS’ WRITING SKILL - Indah Viqrianti Ramli; Ardiana Ardiana (UIN Alauddin Makassar, 2018)
The skills of writing in English are believed to be essential for EFL students. However, the process of learning process is often considered very difficult by many students. One of the reasons is that the students are required to master a lot of conventions in writing, particularly on how they should develop ideas and organize them into a well-written paragraph. As a result, their scores in writing were low. The objective of this research is to investigate the effectiveness of Cognitive Strategy Instruction in Writing (CSIW) strategy to improve the students’ writing skill. A pre-experimental design was employed with one class of the tenth grade students at SMAN 6 Pinrang as sample. Cluster random sampling was applied to select the sample of one group pre-test and post-test design. The number of sample selected was 35 students. The data were obtained through writing test as were analyzed using statistical formula. The findings showed that the students’ mean score in the pre-test was 4.12 and it was improved to be 6.61 in the post-test. Therefore, the statistical computation described that Cognitive Strategy Instruction in Writing (CSIW) strategy was effective to improve the students’ writing skill in recount text. It was supported by the value of t-test that was bigger than the value of t-table (13.10> 2.032). Therefore, the alternative hypothesis (H1) was accepted while the null hypothesis (H0) was rejected.AbstrakKeterampilan menulis dalam Bahasa Inggris diyakini penting bagi siswa EFL. Namun, proses pembelajaran menulis seringkali dianggap sangat sulit oleh banyak siswa. Para siswa memiliki ilmu yang masih sangat minim tentang bagaimana mengembangkan ide-ide dan mengaturnya menjadi paragraf yang ditulis dengan baik. Akibatnya, nilai mereka dalam menulis rendah. Mereka membutuhkan sebuah strategi untuk meningkatkan kemampuan menulis mereka. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas Instruksi Strategi Kognitif dalam Menulis (CSIW) untuk meningkatkan keterampilan menulis siswa. Penelitian ini menggunakan desain pra-eksperimental dengan mengambil sampel siswa kelas sepuluh di SMAN 6 Pinrang. Kluster random sampling diterapkan untuk memilih sampel tersebut dengan jumlah sampel sebesar 35 siswa. Data diperoleh melalui tes tertulis dan dianalisis menggunakan rumus statistik. Hasil dari penelitian ini menunjukkan bahwa nilai rata-rata siswa dalam pre-test adalah 4,12. Nilai tersebut meningkat menjadi 6,61 pada post-test. Oleh karena itu, hasil perhitungan statistik menggambarkan bahwa Instruksi Strategi Kognitif dalam Menulis (CSIW) efektif untuk meningkatkan keterampilan menulis siswa khususnya dalam menulis teks recount. Hal ini didukung oleh nilai t-test yang lebih besar dari nilai t-tabel (13.10> 2.032). Oleh karena itu, dapat disimpulkan bahwa hipotesis alternatif (H1) diterima, sementara hipotesis nol (H0) ditolak.Kata Kunci: Instruksi Strategi Kognitif dalam Menulis (CSIW), Keterampilan Menulis, Pembelajaran Menulis